2021
DOI: 10.1097/coh.0000000000000701
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of drug interactions and adverse reactions in contemporary antiretroviral therapy

Abstract: Purpose of reviewAdvances in antiretroviral therapy (ART) have transformed HIV infection into a chronic and manageable condition. The introduction of potent and more tolerable antiretrovirals (ARVs) with favorable pharmacokinetic profiles has changed the prevalence and nature of drug-drug interactions (DDIs). Here, we review the relevance of DDIs in the era of contemporary ART. Recent findingsManagement of DDIs remains an important challenge with modern ART, primarily due to increased polypharmacy in older per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…4,18 Drug interactions are common among patients with HIV on antiretroviral therapy, which should be considered when starting or intensifying statin therapy for management of CCD. 6,7,19,20 Although pravastatin and pitavastatin are least likely to interact with antiretroviral therapy, rosuvastatin and atorvastatin may be preferred for more intense LDL-C reduction in patients with HIV and CCD. 20,21 Management of hypertriglyceridemia in patients with CCD and HIV should follow standard treatment pathways.…”
Section: Special Populationsmentioning
confidence: 99%
“…4,18 Drug interactions are common among patients with HIV on antiretroviral therapy, which should be considered when starting or intensifying statin therapy for management of CCD. 6,7,19,20 Although pravastatin and pitavastatin are least likely to interact with antiretroviral therapy, rosuvastatin and atorvastatin may be preferred for more intense LDL-C reduction in patients with HIV and CCD. 20,21 Management of hypertriglyceridemia in patients with CCD and HIV should follow standard treatment pathways.…”
Section: Special Populationsmentioning
confidence: 99%
“…In our study cohort, 30% of PEP users reported engaging in chemsex; an additional third had comorbidities, with half of these individuals receiving psychiatric medications. The DOR/3TC/TDF regimen is associated with a lower risk of drug–drug interactions than many other PEP regimens [ 34 ]. This is relevant because of the potential for drug–drug interactions among different PEP regimens recommended in current guidelines, including pharmacokinetic enhancers such as protease inhibitors or EVG-based regimens.…”
Section: Discussionmentioning
confidence: 99%
“…This was likely due to decreased plasma clearance of the antineoplastic agents as the CYP3A4 proteins were being used by the antiretroviral drugs. Previous drug interactions between ritonavir and docetaxel 13,14 as well as boosted antiretrovirals including darunavir boosted with ritonavir 15 have been reported. Strategies to diminish adverse reactions due to drug interactions include switching to antiretrovirals with decreased drug interaction potential, changing co-medications, and altering medication dosage or dosing frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to diminish adverse reactions due to drug interactions include switching to antiretrovirals with decreased drug interaction potential, changing co-medications, and altering medication dosage or dosing frequency. 15 The patient's antiretroviral regimen was subsequently changed to dolutegravir (minor CYP3A4 substrate), doravirine (major CYP3A4 substrate), and valacyclovir (not a CYP3A4 substrate). With this antiretroviral combination, the patient was able to resume therapy with EV and has been tolerating it without major toxicity to date.…”
Section: Discussionmentioning
confidence: 99%